2014
DOI: 10.1139/apnm-2014-0091
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining hydration with a carbohydrate–electrolyte solution improves performance, thermoregulation, and fatigue during an ice hockey scrimmage

Abstract: Research in "stop-and-go" sports has demonstrated that carbohydrate ingestion improves performance and fatigue, and that dehydration of ∼1.5%-2% body mass (BM) loss results in decreased performance, increased fatigue, and increased core temperature. The purpose of this investigation was to assess the physiological, performance, and fatigue-related effects of maintaining hydration with a carbohydrate-electrolyte solution (CES) versus dehydrating by ∼2% BM (no fluid; NF) during a 70-min ice hockey scrimmage. Ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
(56 reference statements)
2
29
0
1
Order By: Relevance
“…This design was undertaken to best represent the efforts of a typical ice hockey shift, where performance is dictated solely by the voluntary efforts of the player, and is consistent with other sport-specific investigations. Perhaps most similar to the present study is that of Linseman et al who observed a preservation of shuttle skating time ( − 0.7s or − 2.4 %) following an on-ice scrimmage when subjects had ingested a CES vs. became mildly dehy-drated ( − 1.9 % BM) [28]. Also, in a sport-specific test of basketball skills performance, Dougherty et al utilized a comprehensive battery of self-selected, work-based performance tests including "suicide sprint" shuttle running, and time to complete 10 court-width sprints.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This design was undertaken to best represent the efforts of a typical ice hockey shift, where performance is dictated solely by the voluntary efforts of the player, and is consistent with other sport-specific investigations. Perhaps most similar to the present study is that of Linseman et al who observed a preservation of shuttle skating time ( − 0.7s or − 2.4 %) following an on-ice scrimmage when subjects had ingested a CES vs. became mildly dehy-drated ( − 1.9 % BM) [28]. Also, in a sport-specific test of basketball skills performance, Dougherty et al utilized a comprehensive battery of self-selected, work-based performance tests including "suicide sprint" shuttle running, and time to complete 10 court-width sprints.…”
Section: Discussionsupporting
confidence: 90%
“…This was similar to findings during a competitive ice hockey game where mean BM loss was 1.3 ± 0.3 % and 8/24 players (33 %) lost 1.8-4.3 % BM [32]. Such hypohydration is generally accepted to impair exercise performance and normal cognition during exercise [43], and our lab has previously demonstrated that when ice hockey players dehydrated by 1.9 % BM during an on-ice scrimmage, they exhibited slower skating speed, more frequent turnovers, and an increased perception of effort [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that sweat loss resulting in decreases in body mass (BM) of as little as 1.5-2 % (mild dehydration) can negatively impact athletic and cognitive performance in numerous intermittent team sports for both male [1][2][3][4][5][6][7][8][9] and female athletes [10][11][12][13][14]. With this in mind, measuring individual sweat rates and hydration habits of athletes can identify players who become mildly dehydrated and are at risk of experiencing impaired performance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively cool environment in which ice-hockey is played, recent research has demonstrated that male hockey players lose large amounts of sweat (1.3-2.6 L/h) during both practices and games [15][16][17][18]. Linseman and colleagues (2014) assessed the effects of mild dehydration on thermoregulation, performance and fatigue during a 70 min on-ice hockey scrimmage [7]. The study consisted of a no fluid trial (NF) with an average BM loss of 1.94 ± 0.1 % and a carbohydrate electrolyte solution trial (CES) where BM was maintained (loss of 0.12 ± 0.1 %).…”
Section: Introductionmentioning
confidence: 99%